Usage of inhalation devices in asthma and chronic obstructive pulmonary disease: a Delphi consensus statement. (March 2014) - Ninane, Vincent; Brusselle, Guy G; Louis, Renaud; Dupont, Lieven; Liistro, Giuseppe; De Backer, Wilfried; Schlesser, Marc; Vincken, Walter
<x xml:space="preserve">Abstract</x> Objectives: The study aimed to assess usage of inhalation devices in asthma and chronic obstructive pulmonary disease (COPD). Methods: In this two-round Delphi survey, 50 experts in asthma and COPD completed a 13-item, Internet-based, self-administered questionnaire about choice of inhalation device, training and monitoring of inhalation techniques, the interchangeability and the role of costs in the selection of inhalation devices. For each item, the median (central tendency) and interquartile ranges (degree of consensus) were calculated. Results: Experts considered that the choice of inhalation device was as important as that of active substance (very good consensus) and should be driven by ease of use (good to very good consensus) and teaching (very good consensus). Experts recommended giving oral and visual instructions (good consensus) and systematic monitoring inhalation techniques. Pulmonologists and paramedics have predominantly educational roles (very good consensus). Experts discouraged inhalation device interchangeability (good consensus) and switching for cost reasons (good to very good consensus) without medical consultation (good consensus). Conclusions: The results of this survey thus suggested that inhalation devices are as important as active substances and training and monitoring are essential in ensuring effective treatment of asthma and COPD. Inhalation device switching without medical consultation should be avoided.